2011
DOI: 10.1159/000327589
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Perilla Seed Oil Supplement Increases Plasma Omega-3 Polyunsaturated Fatty Acids and Ameliorates Immunoglobulin A Nephropathy in High Immunoglobulin A Strain of ddY Mice

Abstract: Background/Aims: The beneficial effects of omega-3 polyunsaturated fatty acids (n–3 PUFA) in the treatment of immunoglobulin A nephropathy (IgAN) have been reported. Perilla frutescens (Linn.) Britton var. frutescens is grown in Eastern Asia and its seed (perilla seed) is rich in α-linolenic acid, an n–3 PUFA. We investigated the antinephritic effects of perilla seed oil in a mouse model of IgAN. Methods: Ten-week-old high IgA ddY mice were fed diets containing either perilla seed oil (PS group) or corn oil (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…There are some differences in the traditional efficacy of PFo, PCa, and PFr . Currently, extensive investigation of the phytochemical and phytopharmacological research of PFo showed that various compounds have been isolated and identified, including flavonoids, volatile oils, fatty acids, triterpenes, phenolic compounds, and others, and these aforementioned compounds should be responsible for the antioxidant, antibacterial, anticancer, antiallergic, and antidepressant activities of PFo. The biological and pharmacological effects including antidiabetic and increasing endometrial receptivity effects of PCa have been confirmed by a number of studies in vitro and in vivo. , These benefits are often attributed to the high content of bioactive compounds, especially phenolic, flavonoids, and essential oil components. , Besides, the PFr also contains many bioactive compounds including phenolic, fatty acids, and flavonoid compounds, , showing excellent antioxidative, antibiotic, and hepatic protection activities. Although these three different medicinal parts of P. frutescens have many pharmacological effects, their pharmacological effects are quite different.…”
Section: Introductionmentioning
confidence: 99%
“…There are some differences in the traditional efficacy of PFo, PCa, and PFr . Currently, extensive investigation of the phytochemical and phytopharmacological research of PFo showed that various compounds have been isolated and identified, including flavonoids, volatile oils, fatty acids, triterpenes, phenolic compounds, and others, and these aforementioned compounds should be responsible for the antioxidant, antibacterial, anticancer, antiallergic, and antidepressant activities of PFo. The biological and pharmacological effects including antidiabetic and increasing endometrial receptivity effects of PCa have been confirmed by a number of studies in vitro and in vivo. , These benefits are often attributed to the high content of bioactive compounds, especially phenolic, flavonoids, and essential oil components. , Besides, the PFr also contains many bioactive compounds including phenolic, fatty acids, and flavonoid compounds, , showing excellent antioxidative, antibiotic, and hepatic protection activities. Although these three different medicinal parts of P. frutescens have many pharmacological effects, their pharmacological effects are quite different.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of the included studies was assessed using SYRCLE’s risk of bias tool for animal studies ( Table 2 ). Only one study randomly allocated animal models to the intervention and control groups [ 35 ]. It is unclear if the other studies randomly allocated animal subjects to a specific intervention.…”
Section: Resultsmentioning
confidence: 99%
“…No study found a high risk of bias in one domain (subject selection). The investigators were not blinded from knowledge of which intervention each animal received during the experiment in all studies performed by Makino et colleagues, while this aspect was unclear for the study performed by Sakurai et al [ 35 ]. These aspects suggest a possible performance bias of the evaluated studies.…”
Section: Resultsmentioning
confidence: 99%
“…EPA and DHA have been shown to reduce the expression of several pro-inflammatory cytokines ( 26 - 30 ) and pro-fibrotic genes ( 31 , 32 ) in mesangial cells and a mouse model of IgAN. Those effects led to a decrease in serum IgA, serum IgA immunocomplexes, the deposition of IgA in the mesangium ( 29 , 30 ), the inhibition of the mesangial cell proliferation ( 33 ) and matrix ( 34 ), and a reduction of proteinuria ( 34 ). These reports indicate that some of the effects of EPA and DHA differ, supporting our hypothesis that the in vivo activities of DHA in patients with IgAN differ from those of EPA and that the two together have pleiotropic renoprotective effects beyond the anti-proteinuric and anti-hypertensive effects.…”
Section: Discussionmentioning
confidence: 99%